Can the SDGs in low-income countries be financed? And should we care? - Ole Winckler Andersen; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2019)
SDGs (The Sustainable Development Goals) are underfinanced in developing countries, especially in low-income countries. This conclusion is based on a review of SDG financing needs and available financing sources - including international private finance, blended finance, remittances, domestic resource mobilization, ODA and debt financing. The underfinancing in low-income countries is substantial, but in a global perspective it constitutes only half a percentage point of world GDP in 2030. To address the underfunding of the SDGs, policy priorities and allocation decisions in developing as well as donor countries must change significantly. Whether this is possible depends on the local and international political contexts. Realistically not all SDGs will be fully funded.
Keywords: 330; UN-Entwicklungsziele; Entwicklungsländer